Caseins as source of bioactive peptides - Silva, Sofia V. (2010)
Biologically active peptides are of particular interest in food science and nutrition because they have been shown to play physiological roles, including opioid-like features, as well as immunostimulating and anti-hypertensive activities, and ability to enhance calcium absorption. Hidden or inactive in the amino-acid sequence of dairy proteins, they can be released or activated in vivo during gastrointestinal digestion, or upstream during food processing via specific, enzyme-mediated proteolysis. Caseins, in either milk or dairy products (e.g. cheese), are important sources of those peptides; their biological significance, their impact on human health and the manufacture of novel functional food ingredients therefrom have been subject to intensive research, which will be briefly presented and critically discussed in this review.